RBA WEB-BASED STICKER ORDERING INFORMATION SYSTEM: WEB-BASED STICKER ORDERING INFORMATION SYSTEM - Adwiya, Rabiatul Adwiya (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2022)
Ordering is an activity that is often carried out when transacting in trade or services between customers and providers of products and services. At printing office the ordering process is used to order sticker prints where the customer can place an order without coming directly to the printer, the problem that occurs is that there is often a difference in data in ordering and ordering financial statements because when placing an order there are still several applications that can be used. lead to a higher error rate. The design of the sticker ordering information system on the printing office Web-based administrator uses a prototype method that defines the workflow of the system starting from the activities of designing applications. The result of this design is a design in the process of making cover letters to archiving cover letters. Web design on this information system uses Draw.io as a diagram editor in making UML, use cases, activity diagrams, ERD and LRS.